SMS mobile encryption on google TM android - Liang, Guoliang. (2011)
In recent year, numbers of mobile subscriber have increase relatively with the improvement of mobile technologies such as IPhone or Android platform. Till September 2010, statistic shows that the Mobile Population Penetration Rate in Singapore is 141.1% and in the third quarter of the year, total number of Short Message Service (SMS) transaction is 2,391,447,400. This result shown that Singaporean is frequently using SMS as communication tools hence SMS will continue to play an important role in the mobile network market. Although SMS have great influence in our daily life, information sent through wireless network can be unsafe. The objective of developing this project is to allow user to send confidential SMS over the air based on AndroidTM Platform using Rivest, Shamir and Adleman (RSA) cryptography algorithm. The main functions of the application consist of Sending/Reading of confidential SMS, adding new secure parties and generating new public-private key pair. In addition, these generated public key will be uploaded to a web based Key Bank for key distribution purpose and in a case of the user misplacing its phone, the user can log on to the system to delete these uploaded public key for security purpose. The development process follows the waterfall model. Upon completion, System testing and Performance testing are conducted to obtain the efficiency and correctness of the result. A set of test cases is designed to facilitate the testing operation.